The Impact of Organizational Learning on Organizational Resilience in the General Administrations of Private Libyan Commercial Banks Case Study: The Bank of Commerce and Development (Economic studies journal, 2025)
The study aimed to identify the impact of organizational learning on organizational flexibility, as well as to know the level of both organizational learning and organizational flexibility in the general management of the Bank of Commerce and Development as a case study. The study followed the case study approach, and the questionnaire was used as a tool to collect the primary study data, which was developed and its validity and reliability coefficient were confirmed. The study was conducted on a sample of (126) employees, who were selected by simple random method from all employees. The data were analyzed using the Statistical Package for Social Sciences (SPSS) program. The study concluded that organizational flexibility, organizational learning and their dimensions had a high level. The study also revealed the existence of a statistically significant effect of organizational learning and its dimensions on organizational flexibility. The study also revealed that the most influential dimension of organizational learning on organizational flexibility is adaptive learning. Finally, the study presented a set of recommendations that are hoped to be followed to enhance the level of organizational flexibility and support organizational learning in the bank under study.
Keywords: Organizational flexibility; Organizational learning; Trade and Development Bank